Dry Eye Disease Terkait Penggunaan Video Display Terminals Pada Pekerja Era Pandemi Covid-19 - Bharata, Irfani Halimah (CV RIFAINSTITUT, 2022)
Dry eye disease (DED) is a multifactorial progressive disease of ocular surface characterized by tear film instability and hyperosmolarity of the precorneal tear film. Patients with DED may experience range of ocular disturbances that may negatively impact their quality of life. The prevalence of DED is increasing among people who work with video display terminals (VDT), especially during the COVID-19 era. Studies have shown the association between DED symptoms and VDT usage. Complete blinking reduction, lacrimal gland hypofunction, Meibomian gland dysfunction, oxidative stress and local inflammation, and blue light phototoxicity are commonly accepted hypothesis. Several approaches are exist to treat and prevent DED among VDT workers.